Entre santos e encantados: a poética de duas irmãs-filhas de santo - MACIEL, Regiane Grinalda (2021)
This Course Completion Work aims to develop a research that values the memories of two sisters, based on their life stories, Renata and Regiane Grinalda Maciel. Part of an experience with the life of my sister, who from her birth brings a story intercortada by several "destinies", and driven by love, materialized in dedication, promise, faith, rites. In order to carry out this work, we seek to dialogue with the studies of memory, orality and theater, in their dialogues and approaches. The theoretical-methodological approach was based on memory studies, based on authors such as Le Goff (2003), Bezerra (2013), Thompson (1992); And performance studies, Shechener (2006), Rangel (2009). The Theater Degree course provides spaces for research like this, by enabling our life history, as important as other subjects, to be studied. Therefore, it opens horizons for research that values the individual and collective memories of the subjects inserted in our society in dialogue with some fields of investigation in the area of the scenic arts, as the studies of the performance, approached in this work.